Inhibition of Borna disease virus replication by an endogenous bornavirus-like element in the ground squirrel genome - Fujino, Kan; Horie, Masayuki; Honda, Tomoyuki; Merriman, Dana K.; Tomonaga, Keizo (Proceedings of the National Academy of Sciences - PNAS, 2014)
Significance Sequences derived from ancient viruses have been shown to make up a substantial part of animal genomes. Bornaviruses, a genus of nonsegmented, negative-sense RNA virus, also have left their DNA copies in the genomes of a number of vertebrate lineages. Recent studies have demonstrated that some endogenous bornavirus-like elements (EBLs) may have acquired functions in their hosts as a result of exaptation. In this study, we show that protein encoded by an EBL in the genome of the thirteen-lined ground squirrel efficiently blocks infection and replication of extant bornavirus. To our knowledge, this is the first report showing that endogenous nonretroviral RNA virus elements may function in antiviral defense, providing a potential role for RNA virus endogenization in host evolution.